El enfoque transaccional en los límites de la empresa - Chaihuaque Dueñas, Bruno (2009)
This article shows the relationship between market and firms through the theory of transactional cost and the relationsthat determine the structure and boundaries of the firm. Using the assumptions from the transactional cost approach,this article proposes some variables that determine optimal organizational structures and their boundaries.